2021
DOI: 10.1016/j.ebr.2021.100486
|View full text |Cite
|
Sign up to set email alerts
|

Changing the culture of care for children and adolescents with functional neurological disorder

Abstract: Highlights There is a pressing need to create a holistic and respectful culture of care for children with FND and their families. An outdated culture of care for children with FND lingers across many health systems. The outdated culture imposes iatrogenic stigma on children and families. Structural, educational, and process interventions can be used to promote change. Essential changes include adoption of FND-informed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
60
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(62 citation statements)
references
References 58 publications
0
60
0
2
Order By: Relevance
“…17 Equally, a dismissive approach to communicating the diagnosis can jeopardise patient confidence in the validity of their illness experience, leaving them feeling angry, ashamed and strongly rejecting discussion of the diagnosis and treatment plan. 18 In our own clinical practice, there is a strong emphasis on fostering optimism and developing a collaborative and individualised management plan with the patient's illness narrative at the centre.…”
Section: Therapeutic Communication Of the Diagnosis Is Keymentioning
confidence: 99%
“…17 Equally, a dismissive approach to communicating the diagnosis can jeopardise patient confidence in the validity of their illness experience, leaving them feeling angry, ashamed and strongly rejecting discussion of the diagnosis and treatment plan. 18 In our own clinical practice, there is a strong emphasis on fostering optimism and developing a collaborative and individualised management plan with the patient's illness narrative at the centre.…”
Section: Therapeutic Communication Of the Diagnosis Is Keymentioning
confidence: 99%
“…Although ReACT appears to be a promising treatment for pediatric FS with an excellent short-term response, additional research is needed to confirm the benefits of ReACT are maintained for at least a year (similar to other treatment studies) [21] given the previous RCT only reported outcomes for 60-days after treatment [20] . Further, given the profound stigma experienced by patients with FND and the potential negative impact of their experiences with stigma on patient outcomes such as treatment efficacy and adherence [22] , [23] , it is necessary to evaluate children and parents’ opinions of ReACT to assess acceptability and continue to refine the intervention. Thus, the aim of the present study is to provide a longitudinal follow-up assessment of children’s FS frequency one year after initial completion of ReACT and evaluate children and parents’ perceptions of their experience in ReACT to determine treatment efficacy and acceptability.…”
Section: Introductionmentioning
confidence: 99%
“…Their case illustrates the common mistakes and misperceptions clinicians and caregivers may have about FNDs. Dr. Kozlowska and colleagues provide similar perspectives with focus on pediatric aspects of FND care [8] . These authors not only provide verbatim narratives from patients and clinicians, they also discuss in detail the specific aspects of those narratives that are incorrect and potentially harmful to patients and their therapeutic relationship with physicians.…”
mentioning
confidence: 97%
“…They also discuss in detail the preferred treatment approaches to patients with FNDs and the differences between pediatric and adult FNDs. This article clearly articulates a framework for treatment approaches that may be more successful in pediatric FNDs and it discusses results of a recently completed randomized controlled trial of “retraining and control therapy (ReACT)” in children and adolescents in whom psychiatric comorbidities are less frequently observed than in adults [8] , [9] . This and another article in this special issue highlight the differences in etiologies, treatment targets, and therapeutic interventions between pediatric and adult FNDs [8] , [10] .…”
mentioning
confidence: 99%
See 1 more Smart Citation